2015
DOI: 10.15561/18189172.2015.1207
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sportsmen’s individual characteristics with the help of mathematical simulation and methods of multi-dimensional analysis

Abstract: Abstract. Purpose: to create the most general mathematical models for determination of sportsmen's individual motor abilities' characteristics and individual features of qualified judo wrestlers' fighting style. Material: in the research 22 sportsmen -judo wrestlers of average weight categories (60-81 kg) participated. Results: model, on the base of which it becomes possible to determine individual characteristics of sportsmen, has been found. With the help of factorial 4 main factors analysis of judo wrestler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
14
0
3
Order By: Relevance
“…This approach is consistent with other studies (Ivashchenko, Yermakova, Cieślicka, & Śukowska, 2015;Kozina, 2015;Ilnytska et al, 2016). The key indices include anaerobic power, values of O 2 -debt, maximal oxygen consumption, maximal respiratory minute volume, HR, Watt-pulse and ventilatory equivalent of standard work, general aerobic potential realization, mechanical efficiency of work, index of myocardial tension, amplitude of P-and R-waves of ECG.…”
Section: Jpes ®supporting
confidence: 89%
See 1 more Smart Citation
“…This approach is consistent with other studies (Ivashchenko, Yermakova, Cieślicka, & Śukowska, 2015;Kozina, 2015;Ilnytska et al, 2016). The key indices include anaerobic power, values of O 2 -debt, maximal oxygen consumption, maximal respiratory minute volume, HR, Watt-pulse and ventilatory equivalent of standard work, general aerobic potential realization, mechanical efficiency of work, index of myocardial tension, amplitude of P-and R-waves of ECG.…”
Section: Jpes ®supporting
confidence: 89%
“…Substantiation of test selection for evaluation of wrestlers' level of fitness (Lozhechka, 2012;Latyshev, 2013), account for athlete individual features (Latyshev, & Korobeynikov, 2013;Kozina, Jagiello, & Jagiello, 2015;Korobeynikov, Latyshev, Latyshev, Goraschenko, & Korobeynikova, 2016), monitoring of athlete's heart rate status (Liu, 2015), the level of basic technical preparation (Iermakov, & Boychenko, 2010;Jagiello, Dornowski, & Wolska, 2014), search for optimum variants to improve work capacity and action performance (Chistyakova, 2012;Mehranpou, Silalerdetkul, Hasani, & Witid, 2015;Tropin, & Pashkov, 2015), account for biomechanical regularities of motor action organization ( Adashevskiy Iermakov, & Gritsyuk, 2010;Adashevskiy, Dylewski, & Iermakov, 2011;Muntian, 2013;Vladimir, & Marian, 2015;Wilke, Fleckenstein, Krause, Vogt, & Banzer, 2016) are of tremendous importance in combat sports. In these cases it is recommended…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics confidently differ in players of different game roles [8,31];  We marked out individual features of sportsmen by condition of their motor abilities. Besides, we found individual styles of qualified sportsmen's duels [32];  We showed influence of trainings in rope parks on indicators of heart beats rate and on senior schoolchildren's quickness. It was found that overcoming rope obstacles helps to receive required physical load as well as feelings, characteristic for extreme kinds of sports.…”
Section: Introductionmentioning
confidence: 78%
“…In our research the methodology for individualization in game sports is used [43,44]. From this point of view the system of a team's combination and individual approach to process of athletes training in aerobics is expansion and addition of results of other researches [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%